ANALISIS YURIDIS PENDAFTARAN TANAH PERKEBUNAN RAKYAT (STUDI DI KABUPATEN ASAHAN) - BOB JULYO FIRSTLY SIAHAAN (PREMISE LAW JURNAL, 2016)
Plantation is one of the biggest economic sectors in North Sumatera Province. Plantations in North Sumatera are dominated by oil palm, rubber, coconut, and cocoa. It is a promising sector for large profit so that legal entities and individuals are very interested in doing their business in plantation. Smallholders’ plantations are managed by individuals who do not have enough capital, compared with those which are managed by corporation. They only have on the average of two hectares or less, while they need sufficient capital to increase production. Not all land areas owned by planters are included in land registration system so that they cannot be used as collateral as it is stipulated in Law No 4/1996. Legal certainty has to be given to land right holders so that there will be the feeling of safety and reduce land conflict, so that what is intended by Article 33, paragraph 3 of the Constitution can be realized for the life of the nation and Indonesia. Keywords: Smallholders’ Plantation, Land Registration, Land Rights